The Nature and Legal Effects of Shareholders Agreements in the Czech and Slovak Private Law and its Interpretation - Brožová, Sandra (European Scientific Journal, ESJ, 2019)
The aim of this article is to capture the nature of interpretation of the commercial and legal phenomenon called shareholders´ agreements. It discusses particularly judicial interpretation in several European jurisdictions. The following research questions are posed: Are the shareholders agreements capable of inducing the informal change of corporate statutes? Isthe prevailing character of the shareholders agreements contractual or corporate? Is it possible to conclude shareholders agreements dealing with voting rights exercise in the course of corporate management? The main focus is to give an overview of the prevailing trends of interpretation against the backdrop of comparison of the Czech and Slovak legal regulation with western Europe´s approach. The results showed that the explicate legal definition and regulation of shareholders agreements in Slovakia on the level of generally binding source of law is rather unique in Europe and that the broad acceptance of shareholders agreement in some western European countries (e.g. Germany, Austria and Netherlands) is very liberal and more extensive that their usual perception in the Czech Republic and in Slovakia.